Automorphic forms and zeta functions: proceedings of the conference in memory of Tsuneo Arakawa : Rikkyo University, Japan, 4-7 September 2004 - Böcherer, Siegfried (World Scientific, 2006)
Preface -- Tsuneo Arakawa and his works -- Estimate of the dimensions of Hilbert modular forms by means of differential operators / Hiroki Aoki -- Marsden-Weinstein reduction, orbits and representations of the Jacobi group / Rolf Berndt -- On Eisenstein series of degree two for squarefree levels and the genus version of the basis problem I / Siegfried Böcherer -- Double zeta values and modular forms / Herbert Gangl, Masanobu Kaneko and Don Zagier -- Type numbers and linear relations of theta series for some general orders of quaternion algebras / Ki-Ichiro Hashimoto -- Skew-holomorphic Jacobi forms of higher degree / Shuichi Hayashida -- A hermitian analog of the Schottky form / M. Hentschel and A. Krieg -- The Siegel series and spherical functions on O(2n)/(O(n) x O(n)) / Yumiko Hironaka and Fumihiro Sato -- Koecher-Maa[symbol] series for real analytic Siegel Eisenstein series / Tomoyoshi Ibukiyama and Hidenori Katsurada -- A short history on investigation of the special values of zeta and L-functions of totally real number fields / Taku Ishii and Takayuki Oda -- Genus theta series, Hecke operators and the basis problem for Eisenstein series / Hidenori Katsurada and Rainer Schulze-Pillot -- The quadratic mean of automorphic L-functions / W. Kohnen, A. Sankaranarayanan and J. Sengupta -- Inner product formula for Kudla lift / Atsushi Murase and Takashi Sugano -- On certain automorphic forms of Sp(1, q) (Arakawa's results and recent progress) / Hiro-Aki Narita -- On modular forms for the paramodular groups / Brooks Roberts and Ralf Schmidt -- SL(2, Z)- invariant spaces spanned by modular units / Nils-Peter Skoruppa and Wolfgang Eholzer.